1995
DOI: 10.1093/jnci/87.18.1365
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Genital Human Papillomavirus Infection as a Risk Factor for Persistent Cervical Dysplasia

Abstract: The natural history of genital HPV infection directly influences the prognosis of cervical dysplasia as measured by persistence of the lesion. Testing for HPV infection may be valuable in the clinical management of women with cervical dysplasia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
396
2
34

Year Published

1997
1997
2006
2006

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 711 publications
(459 citation statements)
references
References 0 publications
20
396
2
34
Order By: Relevance
“…Infection with high-risk, [11,17,21]. Evidence suggests that, in general, cervical cancer develops only in the small proportion of women (<10%) with persistent (or latent) HPV infection [15,23]. HPV type 16 is the most commonly occurring oncogenic HPV type, and is present in y50 % of cervical cancers and high-grade cervical intraepithelial neoplasias (CIN 2/3), and in y25 % of lowgrade cervical intra-epithelial neoplasias (CIN 1).…”
Section: What Causes Cervical Cancer ? Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…Infection with high-risk, [11,17,21]. Evidence suggests that, in general, cervical cancer develops only in the small proportion of women (<10%) with persistent (or latent) HPV infection [15,23]. HPV type 16 is the most commonly occurring oncogenic HPV type, and is present in y50 % of cervical cancers and high-grade cervical intraepithelial neoplasias (CIN 2/3), and in y25 % of lowgrade cervical intra-epithelial neoplasias (CIN 1).…”
Section: What Causes Cervical Cancer ? Human Papillomavirus (Hpv)mentioning
confidence: 99%
“…[1][2][3] Both the length of the infection and a high viral load several years before diagnosis have been shown to increase the risk of developing cervical dysplasia and carcinoma in situ (CIS). [4][5][6] Certain HLA class II alleles, such as DRB1*1501 and DQB1*0602, have been shown to increase the risk for cervical carcinoma, most strongly in HPV 16-positive carcinomas. [7][8][9][10][11][12][13] We have previously shown that the increased carcinoma risk primarily depends on that the alleles render carriers more susceptible to HPV16 infections.…”
mentioning
confidence: 99%
“…Most genital human papillomavirus (HPV) infections are transient: within 2 years of incident infection, HPV DNA becomes undetectable in approximately 90% of women (Ho et al, 1995). Moreover, not all women infected with HPV seroconvert; only about half of all HPV DNA-positive women test positive for corresponding type-specific antibodies using available assays (Kirnbauer et al, 1994;Le Cann et al, 1995).…”
mentioning
confidence: 99%